(untitled) (Studia Prawnicze / The Legal Studies, 1964)
In 1958-1962, doubts were raised as to whether the provisions regulating the contracting agreement should be applied to construction and installation agreements. Moreover, during the work on the draft Civil Code of the Polish People’s Republic carried out at that time, the supporters of economic law made the assertion that the state investment (construction) activities cannot be standardized within the division into civil, administrative and financial law. Finally, the opposite opinion prevailed. The draft Civil Code adopted by the Council of Ministers on 7 February 1963 and submitted to the Sejm contains a special section entitled “Construction Agreement”. Taking into account the specific features that distinguish construction agreements from contracting agreements, however, the draft adheres to the view that the performer of construction work is responsible for the result like a contractorUltimately, the draft provides that “The relevant regulations on the contracting agreements are applied to the consequences [...] of the improper work performance by the contractor, liability for shortcomings in the completed object, as well as the investor’s right to withdraw from the contract before the object completion”. The rights and obligations of the customer of the construction works and the performer (contractor) of the same works are regulated not only by civil law provisions but also by administrative regulations. In particular, the Construction Law published in 1961, which is a codification of already published administrative regulations, vests the investor with an obligation to constantly supervise the construction site, to make decisions on technical, economic, operational and similar issues during construction. If these administrative and legal obligations were reflected directly in the relationship between the contractor and the investor, then one could conclude that the investor was jointly responsible for every contractor’s step which they did not immediately protest. Ultimately, the legal framework of the construction agreement according to which the contractor was responsible before the investor for the work result would not have been justified. However, such a contradiction between administrative regulations and the legal framework seems to be apparent. After all, administrative regulations of the construction law were not issued to weaken the liability of the contractor and were not in their interests. Therefore, in their relations with the investors, the contractors cannot claim that the investors do not properly supervise, so they bear joint responsibility for the improper performance of the contract (agreement). The contractual system in the socialist economy should ensure a strict distribution of duties and automatic control of some economic units by others occupying different positions. Civil law provisions on construction work put the main responsibility on the contractor who, using due diligence, is obliged to carefully examine the documentation delivered to them, check the suitability of the materials delivered, the correctness of the instructions given by the investor, and warn about the possible negative consequences of their application. If, despite this warning, the investor insists on the use of documentation, materials, etc., it begs the question whether the contractor’s obligation to protect public property will not be violated when they fulfil the investor’s order. If we accept the point of view that in any case, when the contractor has doubts about the correctness of the investor’s decision, the contractor should refuse to implement it, and this could slow down progress in the construction. In principle, a refusal can follow only if the contractor is sure of the negative consequences of fulfilling the customer’s order. In other cases, the contractor should adapt to them and will not be be liable for possible negative consequences. Speaking about the contractor’s obligation to “carefully” examine the documentation, materials, etc., we should not forget that the construction company must have construction specialists but may not have experts who would be able to assess the suitability of the documentation for the implementation of the intended industrial or other purposes. Therefore, if an object constructed in accordance with the documentation were found to have defects in terms of the indicated special purposes, the investor and the design office, not the contractor, would be responsible for these defects. The contractor is not responsible for object defects caused by hidden shortcomings of documentation and materials. In case of detection of object defects, the investor should demand the elimination of these defects. If it is not possible, they must reduce the remuneration due accordingly. In both cases, they should claim damages. Considering the socio-economic purpose of warranties for defects, we should first specify that, in terms of the economy as a whole and common interests, the harm caused by the improper work performance is unavoidable. It is not compensated by the fact that the customer will pay the contractor a lower price and receive compensation for damages. Similarly, the elimination of a defect may prevent further increase in losses but will not eliminate losses that have already occurred. After all, the elimination of defects will require the contribution of living and materialized labour which could be used for a production of new goods if the object would not have defects. From general economic point of view, regulations on liability for defects and compensation for damages perform the following three functions: firstly, repressive and preventive; secondly, they must guarantee citizens that the products will be of proper quality and meet the established price; thirdly, in relations between public organizations, the regulations on responsibility for defects ensure the correct result recording. If an enterprise —a manufacturer or a contractor — was not obliged to bear the costs of eliminating defects, or if they received the same payment for a defective item as for an item without a defect, then the results of the enterprise’s work would appear in a distorted form. The quality element of the manufactured object would not have been reflected in its accounting. Considering the functions specified in para. 2 and 3, we can say that the provisions on liability for defects must ensure a balance of mutual obligations, the same liability, with the exception of claims for damages exceeding the so-called “negative interest”, does not depend on the contractor’s fault. In conclusion, we consider the issue of “warranty periods” to which, in the author’s opinion, arbitration practice ascribes the wrong meaning.